Technoscientific Research : Methodological and Ethical Aspects - Morawski, Roman Z. (De Gruyter STEM, 2019)
From the content: Introduction Mathematical modelling Measurement Scientific explanation Context of discovery Context of justification Uncertainty of scientific knowledge Morality and moral philosophy System ofvalues associated with science General principles of moral decision-making Researchethics Methodological and ethical issues related to experimentation Methodological and ethical issues to researchinformation Methodological and ethical issuesrelated to legal protection of intellectual property